Analysis of Choroidal Thickness in Children with Congenital Aniridia. (2nd October 2020) - Chen, Hui; Wu, Xiaohang; Li, Xiaoyan; Chen, Jingjing; Lin, Zhuoling; Chen, Weirong; Lin, Haotian
ABSTRACT: Purpose : To evaluate the choroidal thickness (CT) in children with congenital aniridia in comparison with age-matched controls. Methods : This was a cross-sectional, observational study that included 64 eyes of 32 children with congenital aniridia (aged 5–12 years) and 80 eyes of 40 healthy subjects who were age-matched. In all subjects, subfoveal choroidal thickness (SFCT) was assessed at 750-μm intervals from the fovea to 1.5 mm in the temporal and nasal directions with spectral-domain optical coherence tomography (SD-OCT). Results : The mean SFCT was 207.67 ± 30.99 µm in the aniridic eyes. This SFCT was significantly thinner than that in control eyes (288.55 ± 30.06 µm) ( P < .001). The SFCTs at 1.5 mm and 0.75 mm intervals in the temporal and nasal directions from the fovea were also significantly thinner in eyes with aniridia than control eyes ( P < .001).There was a significant negative correlation between the SFCT and axial length in eyes with aniridia (B = −10.60, 95%CI = −19.31~-1.89, P = .017). Conclusions : The subfoveal and parafoveal CTs were significantly thinner in eyes with congenital aniridia than in control eyes. These choroidal changes could open up a new way for the research related to the pathophysiology of congenital aniridia.